Fly me to the moon of business performance; elevating the organisational performances trough organisational commitment and the mediating role of change management - Azat Elsaman, Hosam; Daud, Zulkiflee; Rashdan Sallehuddin, Mohd (Edelweiss Applied Science and Technology, 2024)
The present research conceptualised the effect of concept organisational commitment on organizational performance in oil and gas sector in UAE and proposed the role of change management as mediating factor. The research aims to illustrate the influence of organisational commitment on organizational performance to craft the factors of change management impacts on this concept. This research conducted after spotted the gap and inconsistency pattern in academic literature for the concept sustainability, stakeholders and CSR as ecological and practical approach to tackle with the current unprecedented situation in the oil and gas sector. The authors adopted conceptual analysis as a theoretical research methodology that focused on examining and clarifying the definitions, meanings and utilisation of study key variables within a certain field, hence It aimed to ensure the consistent and accurate application of these concepts by revealing underlying assumptions and theoretical framework of stakeholder theory and the contemporary business issues. This study successfully conceptualised the effect of organisational commitment(OC) on organizational performance(OP). In addition, this study investigated the role of organizational change management OCM as a mediating variable on the relationship between organisational commitment on organizational performance OP. This research crafted the dynamic flow chart and the theoretical background for the relation of the underpinning stakeholder theory and the variables that effect the organisational performance in the oil sector that led to enrich the understanding and prospects of managers executive of these corporates to utilise that model among their organisations.